Circulating Tissue Inhibitor of Matrix Metalloproteinase-4 (TIMP-4) in Systemic Sclerosis Patients with Elevated Pulmonary Arterial Pressure - Gialafos J. Elias; Moyssakis Ioannis; Psaltopoulou Theodora; Papadopoulos P. Dimitrios; Perea Despoina; Vlasis Kostantinos; Kostopoulos Charalampos; Votteas Vassilios; Sfikakis P. Petros (Hindawi Limited, 2008)
Decreased levels of matrix metalloproteinases (MMPs) or excess levels of their tissue inhibitors (TIMPs) may contribute to dysregulation of extracellular matrix turnover in systemic sclerosis (SSc). In a cross-sectional study of 106 SSc patients, we measured serum levels of TIMP-4 which is preferentially expressed in cardiovascular structures and searched for correlations with simultaneously performed echocardiography measurements of pulmonary artery systolic pressure (PASP), myocardial performance, and pulmonary function tests. TIMP-4, but not MMP-9, levels were significantly raised in patients with SSc than controls. However, in the subgroup of patients with PASP measurements lower to 40 mmHg (n=69), TIMP-4 levels were comparable to controls irrespective of the presence of diffuse or limited skin involvement, or lung fibrosis. Individual PASP measurements suggestive of pulmonary hypertension were associated with increased TIMP-4 serum levels (P=.03), independently of age, extent of skin sclerosis, or lung fibrosis, suggesting a cardiopulmonary vasculature-specific role of TIMP-4 activation in SSc.